The Initial Impact of The Covid-19 Pandemic on Older Workers in Lithuania - Zitikytė, Kristina (Ekonomika, 2022)
The Covid-19 pandemic that began in 2020 presented a new challenge for the labor market participants. This paper discusses the Covid-19 pandemic, highlighting the key challenges that older people can face trying to stay in the labor market for longer in the future, especially if such pandemics continue. Binary response models are used to identify the push-and-pull factors determining the impact of the Covid-19 pandemic on the employment of people aged 55–64 during the pandemic in Lithuania. As the Covid-19 pandemic still continues, most of researchers prefer statistical analysis, comparing employment rates with those of the 2009 economic crisis, to determine the potential impact of the pandemic on employment or by only theoretically discussing the potential impact of the pandemic on the elderly. This paper models the impact of the pandemic on the employment of older people in Lithuania using unique administrative micro-data of State social insurance fund (SSIF). This allows to draw deeper conclusions about how the pandemic affects workers aged 55–64 in Lithuania. The results show that the employment of older people has not been disproportionately impacted by the Covid-19 pandemic, and if such pandemics occur in the future, they may present both limitations and opportunities from the point of view of older people.